MODEL PENINGKATAN KEPATUHAN MEMBAYAR PAJAK - Gunawan Gunawan; Sitti Mispa (AkMen JURNAL ILMIAH, 2022)
This study aims to examine tax morale, socialization, service quality of the tax authorities and the social environment on taxpayer compliance at KPP Madya Makassar. This type of research is quantitative research to test the justification of the proposed hypothesis with statistics. Data was collected through questionnaires which were distributed to respondents with a population of 1,100 individual taxpayers registered at the Makassar Primary Tax Service Office (KPP). The sampling technique in this study is by accidental sampling with the slovin formula so that the total sample is 100 taxpayers. Data analysis used Partial Least Square (PLS) method. Based on data analysis, it was found that tax morale, socialization and social environment had a positive and significant effect on taxpayer compliance at KPP Madya Makassar. While the quality of tax services does not have a significant effect on taxpayer compliance at KPP Madya Makassar.